Risk factors associated with dengue as a communicable disease at Alhajuela parish, Portoviejo, Ecuador - Solís, Abel A.; Mastarreno, Judith J.; Menéndez, Maholy J.; Fernández, Juan G. (Revista Gregoriana de Ciencias de la Salud, 2024)
Dengue is an acute and systemic viral infectious disease, of sudden onset, caused by any of its four serotypes, transmitted by female Aedes aegypti mosquitoes, through their bites. Currently it is one of the most important arboviruses that affects man and is considered a health problem for the world. The objective of this research was to evaluate the knowledge, preventive practices and perceptions about dengue among the population of the Alhajuela parish in Portoviejo, Ecuador. For this, a cross-sectional observational study was carried out, with a sample of 45 residents of the parish. Data collection was carried out using a structured survey that contained demographic questions, questions on dengue knowledge, risk factors, and prevention practices. The population has little knowledge about dengue, its form of contagion and its preventive measures, as well as its means of transmission, which is why adequate measures are not implemented in the population to avoid the replication of the vector and prevention of the bite. Education is a fundamental part of dengue prevention, so knowledge about the risk factors associated with dengue is necessary to control this vector. It is essential that there be health personnel trained to educate the population and the active participation of the community.